Enhanced P-cycling with stylosanthes (Stylosanthes guianensis) in upland rice-based cropping systems in Madagascar - CGIAR Research Program on Rice (2020)
Accumulated the evidence from pot and field trials that Stylosanthes guianensis has high solubilization capacity of Fe-bound P in soils, superior P uptakes than maize, rice, and soybean, and increases the subsequent rice yield relative to those grown after other crops under typical P-deficient uplands in the region.